CAPriCORN: Chicago Area Patient-Centered Outcomes Research Network. (12th May 2014) - Kho, Abel N; Hynes, Denise M; Goel, Satyender; Solomonides, Anthony E; Price, Ron; Hota, Bala; Sims, Shannon A; Bahroos, Neil; Angulo, Francisco; Trick, William E; Tarlov, Elizabeth; Rachman, Fred D; et al.
Abstract: The Chicago Area Patient-Centered Outcomes Research Network (CAPriCORN) represents an unprecedented collaboration across diverse healthcare institutions including private, county, and state hospitals and health systems, a consortium of Federally Qualified Health Centers, and two Department of Veterans Affairs hospitals. CAPriCORN builds on the strengths of our institutions to develop a cross-cutting infrastructure for sustainable and patient-centered comparative effectiveness research in Chicago. Unique aspects include collaboration with the University HealthSystem Consortium to aggregate data across sites, a centralized communication center to integrate patient recruitment with the data infrastructure, and a centralized institutional review board to ensure a strong and efficient human subject protection program. With coordination by the Chicago Community Trust and the Illinois Medical District Commission, CAPriCORN will model how healthcare institutions can overcome barriers of data integration, marketplace competition, and care fragmentation to develop, test, and implement strategies to improve care for diverse populations and reduce health disparities.